Ageism: can a museum exhibit make a difference?. (21st June 2020) - Fruhauf, Moran; Doron, Israel (Issi); Palgi, Yuval
ABSTRACT: Ageism is a key challenge to today's aging societies. "Dialogue with Time" is an original Israeli interactive museum exhibit that aims to change negative ageist attitudes by creating a meaningful and stereotype-breaking encounter between visitors and old age. The objective of this study was to examine whether the exhibition reduces ageist attitudes among its visitors. The study employed a comparative pre-post structure with a comparison group. A closed-answer questionnaire was supplied to 100 participants in the experimental group, visitors to the "Dialogue with Time" exhibit, and to 100 participants in the control group. Participants were asked to complete the questionnaire before entering the exhibits and again after experiencing them. Changes in the level of ageism were measured using the Farboni Scale of Ageism. A significant reduction in ageism attitudes was shown in the experimental group when comparing before and after the visit, t(91) = 11.75, p = 0.001, with a good effect size of Cohen's d = 0.50, whereas in the control group there was no significant change, t(76) = 0.05, p = 0.95, and a weak effect size of Cohen's d = 0.00. The findings indicate that combating ageism can also be sustained by means of museum exhibits. We recommend that museums and other similar public institutions (e.g. art galleries, exhibition halls) use public spaces to advance multigenerational exposure to positive images of aging.